"Swan Neck Deformity" of the Second Toe Corrected by Flexor Digitorum Longus to Flexor Digitorum Brevis Tenodesis. Issue 2 (April 2015) - Lui, Tun Hing
"Swan neck deformity" of the second toe is a rare deformity. It is a hyperextension of the proximal interphalangeal joint. The patient may complain of painful callosity underneath the proximal interphalangeal joint. Surgical correction should be considered if conservative treatment fails to relieve the pressure point. The optimal surgical option for this deformity has not yet been defined. We report a case of swan neck deformity of the second toe that was successfully corrected by flexor digitorum longus to brevis tenodesis. Levels of Evidence: Therapeutic Level IV: Case Report